(untitled) (BioLaw Journal - Rivista di BioDiritto, 2025)
This contribution reflects on the condition of individuals held in Italy’s Centri di permanenza per i rimpatri (CPRs), questioning which fundamental rights remain effectively protected for those deprived of their liberty. Starting from the principle that fundamental rights must apply to all individuals, it challenges the continuing influence of status civitatis in determining concrete access to rights that the Constitution proclaims as universal. The analysis focuses in particular on the progressive erosion of the safeguards surrounding the personal liberty of non-EU nationals, showing how administrative detention within CPRs is often accompanied by a weakening of other fundamental rights, including the right to health. The paradox of “detained freedom” thus becomes the starting point for this introductory reflection in the present issue, shedding light on the ambiguities of a system that, while operating within the bounds of formal legality, appears to diverge from constitutional principles and the core values of the rule of law.